PERAN MODERASI BERAGAMA TERHADAP PENGARUH LITERASI DIGITAL PADA ADIKSI INTERNET: STUDI PADA MAHASISWA DI KAMPUS MODERAT - Arya Fendha Ibnu Shina; Sari, Ferra Puspito; Shofi'unnafi (UIN Sunan Kalijaga, 2024)
Indonesia is one of the countries with the largest number of internet users in the world. The highest internet penetration is the younger generation. The high internet penetration among the younger generation is certainly a challenge for various parties considering the potential for unhealthy internet behavior, namely internet addiction. Individuals who have digital skills will be able to manage their lives in the real and digital world. This balanced attitude is closely related to a moderate attitude in religion. This research tries to examine the role of religious moderation on the influence of digital literacy on students' internet addiction on moderate campuses. The respondents in this research were 50 students of UIN Sunan Kalijaga and 50 students of UIN Salatiga who were taken using a stratified random sampling technique. The analytical method used is a regression model with mediating variables. The results of this study prove that religious moderation has a significant negative effect on internet addiction. On the other hand, digital literacy has a significant positive effect on religious moderation and a significant negative effect on internet addiction. However, religious moderation does not significantly mediate the influence of digital literacy on internet addiction